A Reception Study On Disinformation Of Covid-19 Vaccine Messages In Social Media Virtual Communities - Sinta Lestari (FAKULTAS DAKWAH UIN SALATIGA, 2023)
Disinformation messages about the Covid-19 vaccine are circulating in the community. This of course intersects with social, health, religious and political issues. One of the issues that is widely spread is about the Covid-19 vaccine, which has side effects when injected into a person's body, and contains dangerous and non-halal ingredients. This issue is widespread on social media, one of which is the various virtual WhatsApp communities in society. This article attempts to provide an explanation of this phenomenon from the Ecoding/Deccoding lens and the Interpretive Community. Data collection was carried out using in-depth interviews with three informants. The results of the study show that audiences using their life history positions, interpretive communities and their limited social communities also strengthen their meaning of this issue. This indicates that the text in the community is no longer seen as an extension of the message or addition of information, but is shown to maintain a community in the community in a relatively temporary period.